Immunogenicity and protective response induced by recombinant Brucella abortus proteins Adk, SecB and combination of these two recombinant proteins against a virulent strain B. abortus 544 infection in BALB/c mice. (June 2020) - Huy, Tran Xuan Ngoc; Bernardo Reyes, Alisha Wehdnesday; Vu, Son Hai; Arayan, Lauren Togonon; Hop, Huynh Tan; Min, WonGi; Lee, Hu Jang; Lee, John Hwa; Kim, Suk
Abstract: In this study, two recombinant proteins encoded by Brucella abortus genes Adk and SecB were evaluated as single subunit vaccine (SSV) as well as combined subunit vaccine (CSV) against B. abortus infection in BALB/c mice. These genes were cloned into pcold-TF expression system and recombinant proteins were expressed in Escherichia coli DH5α. The immunoreactivity of purified rAdk and rSecB was analyzed by immunoblotting showing that purified rAdk and rSecB as well as pcold-TF vector strongly reacted with Brucella -positive serum. Mice were immunized intraperitoneally with SSVs, CSV, pcold-TF, RB51 and PBS. The analysis of cytokine revealed that SSVs and CSV can strongly induce production of proinflammatory cytokines TNF and IL-6, suggesting that these subunit vaccines elicited innate immune response, particularly, activated antimicrobial mechanism of macrophages to limit the initial infection. On the other hand, immunization with SSVs and CSV elicited strong IFN-γ production and decreased IL-10 production compared to PBS group. The secretion profiles of IFN-γ and IL-10 together with an enhancement of blood CD4 + population and significantly induced specific IgG1 and IgG2a antibodies indicated that SSVs and CSV induced not only humoral immunity but also T helper 1 T cell immunity. Finally, spleen proliferation and bacterial burden in the spleen of mice vaccinated with these subunit vaccines were significantly lower than those of PBS group, which conferred significant protection against B. abortus infection. Altogether, the potential of these antigens of B. abortus could be prospective candidates to develop subunit vaccines against brucellosis. Highlights: B. abortus Adk and SecB are cloned into a pcold-TF vector. SSV or CSV with rAdk and rSecB induced a high humoral immunity. SSV or CSV with rAdk and rSecB induced CD4 + T cells differentiation. SSV or CSV with rAdk and rSecB showed significant protection against Brucella.